Consumers' willingness to pay for safe and quality milk: Evidence from experimental auctions in Rwanda - Habiyaremye, Naphtal; Mtimet, Nadhem; Ouma, Emily A.; Obare, G.A. (Wiley, 2023)
A major concern of the Rwandan government and other dairy stakeholders is the safety and quality of milk that goes through informal delivery systems until it gets to the consumers. Although the government introduced the dairy best practices scheme that stipulates standards and practices for proper handling of raw milk, consumers' willingness to pay (WTP) for such milk has not yet been assessed. It is also unclear whether consumers are aware of and/or value the safety- and quality-related information on types of milk sold in different marketing channels. In this study, we use the second price auction mechanism to elicit consumers' WTP for pasteurized but unpackaged milk in Rwanda and we estimate the effect of providing safety- and quality-related information on WTP using the random-effect Tobit model. Our results show that consumers are willing to pay a price premium for safe and quality milk, implying that there is an opportunity for market transformation in the dairy sector. Furthermore, we find a positive and significant effect of providing information to consumers on WTP for safe and quality milk. Based on our results, we recommend policies that promote private sector investments in upscaling of milk zones and the establishment of milk-dispensing machines selling this type of milk. There is also a need for information campaigns that increase consumers' knowledge and awareness of the quality of milk consumed. [EconLit Citations: C34, C91, D12, D44, M31].